Transforming Process Safety and Accident Prevention in Heavy Industries with Inherently Safer Design and Innovative HSSEQ Technologies - Bahar, Zeynep; Havva, Duygu Bilgen; Orcun, Sarioguz (International Journal of Scientific Research and Management (IJSRM), 2025)
The scenario of industrial safety has been shifting significantly within the last 50 years, with the meaning of which is the transition to the design that is inherently safe (ISD) as the most effective tool for preventing hazards. It has been stated statistically that industrial accidents can be reduced by as much as 85 percent through the systematic delivery of the principles of ISD, which are referred to as minimization, substitution, moderation, and simplification. In this paper, we are taking a historical look at the development of ISD since the post-Flixborough period, its integration into the contemporary regulation, and the interaction of technology, human factors, and safety performance. There is a focus on measurable performance indicators, financial value, and life-cycle principles of implementation, through the facility life stages. High technologies, including digital twins, real-time monitoring systems, and predictive analytics, are mentioned as the factors contributing to a more rapid adoption of ISD, whereas human factors engineering is mentioned as one of the key factors ensuring sustained operations safety. In the findings, it was confirmed that the ISD actually enhances the implementation of process safety and regulatory compliance, besides bringing huge savings, lower insurance premiums, and enhancing the emergency process both in terms of cost and time. This study highlights the timelessness of the mission to eradicate hazards at the source as the only foolproof method of ensuring industrial processes are not jeopardised in the age of Industry 4.0 and beyond.